Knowledge, its creation, distribution, and economic significance - Machlup, Fritz (Princeton University Press, 1980)
Contents: Vol 1 presents the conceptual framework for this inquiry and falls into three part: Types of Knowledge, Qualities of Knowledge, and Knowledge as a product